Development of master-slave robotic hand for Mirror Visual Feedback (MVF) therapy - Mohd Ali, A. M.; Ambar, R.; M. Wahi, A. J.; Abdul Jamil, M. M. (UniKLBMI, 2011)
Various human limbs rehabilitation research has been conducted for incorporating robotic technologies in rehabilitation process. It has been proved that robot-based therapy can improve human limbs sensory-motor functions after stroke or injuries due to cerebral vascular accident (CVA). Mirror Visual Feedback (MVF) therapy or mirror therapy is a method introduced back in early 1990s, which is based on mirror illusion to help patient’s limb practice due to paralyze, post-stroke or amputated. MVF could be combined with robotic arm to enhance its effect in improving the affected limb’s sensory-motor function and reduce pain caused by ‘phantom limb’. The purpose of our project is to design and develop a master-slave system robotic hand which can be a substitution for the paralyzed hand in MVF therapy to aid in recovery process of patients upper limb function. The project involves an Arduino microcontroller for the instrumentation, communication and controlling applications. A series of flex sensors are fitted in a master glove to get reading from the movement of human fingers. Microcontroller will further use this information to control multiple servos that controls the movement of slave robotic hand.